Co-production of knowledge and reconfiguration of the environmental struggles in Córdoba province, Argentina (2000 – 2025) - Diaz, Maria Guillermina; Favre, Joaquín Ulises Deon (Geografares, 2026)
This study analyses the nature of the links between the scientific and academic sector and collective actors against a backdrop of growing socio-territorial conflict in the province of Córdoba over the last 25 years, with a focus on processes of knowledge co-production. It is based on the authors’ doctoral research and adopts a qualitative approach combining interviews, documentary analysis, participant observation, participatory mapping and participation in assembly-based forums. The results reveal a recent reconfiguration of these links, marked by tensions between territorialised co-production practices and more institutionalised forms of scientific production, as well as by disputes surrounding the legitimacy of academic knowledge. It is concluded that co-production constitutes a contested field, but is key to the defence of territories and the commons, which requires strengthening situated and horizontal links between science and communities.